PENGARUH PENDEKATAN TARL MODEL PJBL TERHADAP HASIL BELAJAR SISWA MATERI STRUKTUR BUMI KELAS VB SDN BENDUNGAN SEMARANG - Ghaisani Arta Pramesi; Joko Siswanto (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
This research aims to improve student learning outcomes by applying the Teaching at the Right Level approach with the Project Based Learning learning model. The research subjects consisted of 27 students class VB at SDN Bendungan Semarang. This research has four planning stages including; action; observation; and reflection. The results of the research show that there has been an increase in student learning outcomes in the content of Natural and Social Sciences lessons on the structure of the earth. The percentage increase in individual learning outcomes of students from the posttest and pretest was 58%, having reached the Minimum Completeness Criteria value, and experienced an increase in the learning process